1992
DOI: 10.1002/ijc.2910500121
|View full text |Cite
|
Sign up to set email alerts
|

Lethal deformation of cancer cells in the microcirculation: A potential rate regulator of hematogenous metastasis

Abstract: The hypothesis has been advanced that deformation-induced lethal mechanical trauma, resulting in surface-membrane rupture, is inflicted on circulating cancer cells trapped in the microcirculation, and that this rapid cell-killing mechanism is a potentially important rate regulator for hematogenous metastasis. We describe and discuss an in vivo test of this hypothesis. Vital fluorescence microscopy was performed on the microcirculation of cremaster muscle preparations in mice, following retrograde injections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 15 publications
1
88
3
Order By: Relevance
“…32,33 Deformation-induced mechanical trauma and immune-mediated host cell killing have also been implicated in the intravascular death of tumor cells. 31,34,35 The data that we have presented here demonstrate that the local release of NO at the site of tumor cell arrest contributes to this intravascular cytotoxicity although the limited survival of tumor cells even in mice deficient in eNOS would suggest that other factors must play a role as well.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…32,33 Deformation-induced mechanical trauma and immune-mediated host cell killing have also been implicated in the intravascular death of tumor cells. 31,34,35 The data that we have presented here demonstrate that the local release of NO at the site of tumor cell arrest contributes to this intravascular cytotoxicity although the limited survival of tumor cells even in mice deficient in eNOS would suggest that other factors must play a role as well.…”
Section: Discussionmentioning
confidence: 72%
“…23,30,31 Wong and colleagues 32 demonstrated that this cell death in the lung was because of apoptosis and the observations of our lab in the liver would suggest that the death of these cells by apoptosis is a frequent event. 5 The importance of apoptosis in the regulation of pulmonary metastasis is evident both because inhibition of apoptosis by overexpression of bcl-2 leads to more metastasis and because metastatic cells undergo markedly less apoptosis than nonmetastatic cells after arrest in the lung.…”
Section: Discussionmentioning
confidence: 72%
“…Mechanical forces created by arrest can not only cause tumor cell deformation to kill the cells by surface-membrane rupture, 25 but can also trigger the release of NO in the sinusoids, which is cytotoxic to the tumor cells, and cause them to undergo apoptosis and/or necrosis. 9,10 Our previous studies have demonstrated that the rate of apoptosis is significantly higher in the sinusoids compared to the TPV.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 1x10 6 tumour cells are released into the bloodstream on a daily basis (32). The majority of these are destroyed by the immune system (33), while many more are destroyed by haemodynamic forces (34). A very small proportion of extravasated CTCs (~2%) are capable of dividing and forming micro-metastases, while an even smaller number (0.02%) can evolve into fullyfledged distant tumours (35).…”
Section: Are Ctcs Pre-metastatic Cells?mentioning
confidence: 99%